QOMAT BUZILISHINING OLDINI OLISH UCHUN BOLALAR KIYIMIGA QO'YILADIGAN TALABLARNI ISHLAB CHIQISH - D.X.Isayeva, R.X.Salimbekova (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
Currently, posture impairment is one of the common pathologies among primary school children. The article sets out the requirements for creating clothing that forms a normal posture.